Analysis of Consumer Preferences for Beef at Market of Traditionaly - Lumenta, Ingriet D. R; Lainawa, Jolyanis; Lumy, Tilly F. D. (Jambura Journal of Animal Science, 2025)
The purpose of this study was to determine and analyze the relationship between beef attributes (meat color, meat tenderness, meat aroma, and meat price) with consumer preferences in the decision to buy beef at the Bersahati Traditional Market. This study was conducted at Bersehati Market, Manado City from December 2024 to January 2025. The determination of the sample of consumer respondents used the accidental sampling method of 50 people. The data were analyzed using Chi Square analysis, namely to determine the relationship between beef attributes and consumer preferences at Bersehati Market, Manado City. The results of the Chi-Square analysis showed that the attributes of meat color, meat tenderness and meat aroma have a relationship with consumer preferences for beef at the Bersehati Market in Manado City, while the price attribute has no relationship with consumer preferences. The conclusion in this study, the attributes that consumers consider most in the decision to buy beef at the Bersehati Market in Manado City are meat color, meat tenderness, and meat aroma. The meat price attribute does not affect consumer demand for beef, even though the price has increased.